Cognitive ecologies and the history of remembering: religion, education and memory in early modern England - Tribble, Evelyn B. (Palgrave Macmillan memory studies, 2011)
"This book unites research in philosophy and cognitive science with cultural history to re-examine memory in early modern religious practices. Offering an ecological approach to memory and culture, it argues that models derived from Extended Mind and Distributed Cognition can bridge the gap between individual and social models of memory"--